PREVALENCE OF STUNTING EVENTS IN CHILDREN AGED 6-59 MONTHS: A METHA ANALYSYS - Lina Darmayanti Bainuan; Poppy Wijayanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Stunting becomes a very serious problem because it is associated with a greater risk of pain and death, obesity, and future non-communicable diseases, short adults. Stunting is an intergenerational problem in the world. This study is a meta-analysis study and a systematic study. Researchers defined the feasibility criteria using the PICO model: the population of children is 6-59 months, intervention is non-exclusive breastfeeding, comparison is exclusive breastfeeding and outcome is stunting. The articles used were obtained from several electronic databases including PubMed, Science Direct and google Scholar. The articles used in this study are articles that have been published from 2018-2022. The process of searching for research data using the search words Exclusive breastfeeding AND Stunting AND 6-59 months AND Cross-Sectional AND Adjusted Odds Ratio Articles were collected using prisma diagrams and analyzed using the Review Manager 5.4 application. The results of the meta-analysis study in this study there are 3 articles consisting of the State of Ethiopia. Breastfeeding cannot exclusively increase the risk of stunting in children (aOR= 1.20; CI 95%= 0.49 to 2.91; I2= 89%) exclusive breastfeeding affects the incidence of stunting in children aged 6-59 months.